Antimutagenic and anticoagulant therapeutic effects of Ag/Ag2O nanoparticles from Olea europaea leaf extract: mitigating metribuzin-induced hepato-and nephrotoxicity - Azzi, Manel; Laib, Ibtissam; Bouafia, Abderrhmane; Medila, Ifriqya; Tliba, Ali; Laouini, Salah Eddine; Alsaeedi, Huda; Cornu, David; Bechelany, Mikhael; Barhoum, Ahmed (Frontiers in Pharmacology, 2024)
Background: Silver nanoparticles (Ag/Ag₂O NPs) have garnered attention for their potent antioxidant, antimicrobial, and anti-inflammatory properties, showing promise for therapeutic applications, particularly in mitigating chemical-induced toxicity.Objective: This study aimed to synthesize Ag/Ag₂O NPs using Olea europaea (olive) leaf extract as a green, eco-friendly reducing agent and evaluate their protective effects against metribuzin-induced toxicity in Wistar rats, focusing on oxidative stress, hematological parameters, and lipid profiles, with specific dose optimization.Methodology: Ag/Ag₂O NPs were synthesized using Olea europaea leaf extract, and their properties were confirmed via XRD, FTIR, SEM, EDS, and UV-visible spectroscopy. Wistar rats exposed to metribuzin (110 mg/kg/day) were treated with two doses of Ag/Ag₂O NPs (0.062 mg/kg and 0.125 mg/kg). Hematological and biochemical markers were assessed to evaluate the NPs' protective effects.Results: Physicochemical characterization confirmed the successful formation of Ag/Ag₂O NPs loaded with phytochemicals, exhibiting crystallite sizes of 23 nm and 19 nm, a particle size of 25 nm, and significant peaks in XRD, FTIR, and UV-Vis spectra indicating the formation of Ag/Ag₂O. Metribuzin exposure led to significant hematological disruptions (elevated WBC, reduced RBC and hemoglobin) and worsened lipid profiles (increased cholesterol, LDL, and triglycerides). The lower NP dose (0.062 mg/kg) improved WBC, RBC, hemoglobin, and platelet counts, normalized lipid levels, and positively influenced biochemical markers such as serum creatinine and uric acid. In contrast, the higher NP dose 3 (0.125 mg/kg) showed mixed results, with some improvements but an increase in triglycerides and continued elevation of ASAT and ALAT enzyme levels.Ag/Ag₂O NPs synthesized via green methods using olive leaf extract effectively mitigated metribuzin-induced toxicity, especially at lower doses, by improving oxidative stress markers and hematological and biochemical profiles. Dose optimization is crucial to maximize therapeutic benefits and minimize adverse effects, underscoring their potential in treating chemical-induced toxicity.